Epigallocatechin-3-Gallate Promotes the in vitro Maturation and Embryo Development Following IVF of Porcine Oocytes - Huang K; Li C; Gao F; Fan Y; Zeng F; Meng L; Li L; Zhang S; Wei H (Dove Medical Press, 2021)
Kangfa Huang,1 Chengde Li,1 Fenglei Gao,2 Yushan Fan,1 Fanwen Zeng,1 Li Meng,1 Li Li,1 Shouquan Zhang,1 Hengxi Wei1 1National Engineering Research Center for Breeding Swine Industry, Guangdong Provincial Key Laboratory of Agro-Animal Genomics and Molecular Breeding, College of Animal Science, South China Agricultural University, Guangzhou, 510642, People’s Republic of China; 2Department of Tropical Agriculture and Forestry, College of Guangdong Agriculture Industry Business Polytechnic, Guangzhou, Guangdong, 510507, People’s Republic of ChinaCorrespondence: Hengxi WeiNational Engineering Research Center for Breeding Swine Industry, Guangdong Provincial Key Laboratory of Agro-Animal Genomics and Molecular Breeding, College of Animal Science, South China Agricultural University, Guangzhou, 510642, People’s Republic of ChinaTel +86-20-85284869Email weihengxi@scau.edu.cnPurpose: Epigallocatechin-3-gallate (EGCG) is a major ingredient of catechin polyphenols and exerts protective effects because of its strong antioxidant properties. As far as we know, there is still a lack of systematic research on the effects of EGCG on the in vitro maturation (IVM) and in vitro fertilization (IVF) of porcine oocytes. The present study aimed to determine the effects of EGCG on the IVM and IVF of porcine oocytes.Methods: Porcine oocytes were treated with different concentrations of EGCG (5, 10 and 20 μM), and the cumulus cell expansion, oocyte maturation rate, reactive oxygen species (ROS), glutathione (GSH) and malondialdehyde (MDA) levels, total antioxidant capacity were determined. The mRNA expression levels of oxidative stress- and apoptosis-associated genes were determined by quantitative real-time PCR. The cleavage rate and blastocyst rate of oocytes after 10 μM EGCG treatment during IVM and IVF were also evaluated.Results: EGCG at 5, 10 and 20 μM significantly promoted cumulus cell expansion, and EGCG at 10 μM increased the oocyte maturation rate. EGCG (10 μM) treatment reduced the ROS and MDA levels, while increased the antioxidant capacity and GSH concentrations in the mature oocytes. The qRT-PCR results showed that EGCG treatment up-regulated the mRNA expression of catalase, glutathione peroxidase and superoxide dismutase in the mature oocytes. In addition, EGCG treatment also decreased the mRNA expression levels of Bax and caspase-3 and increased the Bcl-2 mRNA expression level in the mature oocytes. In addition, the cleavage rate and blastocyst rate of oocytes treated with 10 μM EGCG during IVM and IVF were significantly higher than those of the control group.Conclusion: Our results suggest that EGCG promotes the in vitro maturation and embryo development following IVF of porcine oocytes. The protective effects of EGCG on the oocytes may be associated with its antioxidant and anti-apoptosis properties.Keywords: EGCG, porcine oocytes, IVM, antioxidant, anti-apoptosis, IVF